Shear strength prediction of deep beams using strut-and-tie method - Wong, Shirley Chin Ling. (2008)
The main objective of the study was to predict the ultimate shear strength of reinforced concrete deep beams using a proposed analytical strut-and-tie model and finite element method. Many of the current design codes of practice are still based on empirical equations and are conservative, therefore there is a need to provide a simple and analytical method to predict the shear strength of deep beams.